Marriage and families in Bosnia and neighbors during the Middle ages - Spahić, Midhat (Historical Thought, 2025)
This article will be treated issues of marriage, the position of women in society and family relations in the Western Balkans teritories in the High and Late Middle Ages. Special focus will be directed to the area of Croatian and Bosnia and Herzegovina in the Middle Ages with a brief overview of conditions in Western Europe, especially France. During the high and late Middle Ages, the Church has sought to regulate marriage customs and put them under his control. In the mediaeval Bosnian state was ruled by specific religious occasions, and most reputation enjoyed Bosnian Church, which was reflected in the different understanding of marriage in relation to other European countries.